Dimeric sorting code for concentrative cargo selection by the COPII coat - Nie, Chao; 聂超; Wang, Huimin; 王惠敏; Wang, Rui; 王锐; Ginsburg, David; Chen, Xiao-Wei; 陈晓伟 (Proceedings of the National Academy of Sciences - PNAS, 2018)
The flow of cargo vesicles along the secretory pathway requires concerted action among various regulators. The COPII complex, assembled by the activated SAR1 GTPases on the surface of the endoplasmic reticulum, orchestrates protein interactions to package cargos and generate transport vesicles en route to the Golgi. The dynamic nature of COPII, however, hinders analysis with conventional biochemical assays. Here we apply proximity-dependent biotinylation labeling to capture the dynamics of COPII transport in cells. When SAR1B was fused with a promiscuous biotin ligase, BirA*, the fusion protein SAR1B-BirA* biotinylates and thus enables the capture of COPII machinery and cargos in a GTP-dependent manner. Biochemical and pulse–chase imaging experiments demonstrate that the COPII coat undergoes a dynamic cycle of engagement–disengagement with the transmembrane cargo receptor LMAN1/ERGIC53. LMAN1 undergoes a process of concentrative sorting by the COPII coat, via a dimeric sorting code generated by oligomerization of the cargo receptor. Similar oligomerization events have been observed with other COPII sorting signals, suggesting that dimeric/multimeric sorting codes may serve as a general mechanism to generate selectivity of cargo sorting.